General motors: A financialized account of corporate behaviour 1909–1940. Issue 4 (December 2016) - Maielli, Giuliano; Haslam, Colin
Highlights: General Motors is a key case study in Alfred Chandler's (1962) text 'Strategy and Structure'. US corporations are now financialized with this 'new-economy business model' displacing the 'old-economy' productive business model. We find that many elements of a financialized firm/new economy business model influenced corporate behaviour at GM during its early development phase 1909–1940. This study on GM explores to what extent the financialization of a non-financial corporation not only modified corporate behaviour but also transformed financial performance. Abstract: This paper constructs an alternative account of resource stewardship at General Motors (GM) during the period 1909–1940. Alfred Chandler employed GM in his text 'Strategy and Structure' to explain the development of the modern corporation. This understanding can be employed to contrast an 'old-economy' with a 'new-economy' financialized corporate business model. In this paper we find that many elements of the financialized firm were present in the early history of GM's development. Our analysis reveals the financialization of a non-financial corporation and how this influenced corporate behaviour and impacted on financial performance at GM during the period 1909–1940.